Rapid Method for Analyzing Gadolinium Binding Activity using Colorimetric Assay Employing PAR - Meri Ayurini; Tony Ekkelenkamp; Jos Paulusse; J.F.J. Engbersen (Jurnal Kimia Valensi, 2019)
Pada penelitian ini, kami mempelajari colorimetric assay yang melibatkan 4-(2-pyridilazo)-resorcinol (PAR) untuk analisis kuantitatif jumlah gadolinium bebas dan yang terikat dengan ligan dalam sistem. Penelitian ini adalah studi awal untuk mengamati pola kompleksasi antara Gd3+ dan molekul target yang dilakukan dalam 100 mM bufer MES pH 5.5. Konstanta pengikatan (Log K) dari kompleks Gd3+-PAR (1-1) pada pH 5.5 adalah     4.41 ± 0.09 M-1. Karena metode ini hanya menggunakan UV-Vis Spektroskopi, disimpulkan bahwa colorimetric assay yang melibatkan PAR adalah metode yang cepat dan murah untuk menganalisis aktivitas pengikatan antara Gd3+ dan ligan target. Katakunci: Gadolinium, colorimetric assay, agen pengkontras MRI. In this research, we study a colorimetric assay employing 4-(2-pyridylazo)-resorcinol (PAR) for quantifying the chelated and free gadolinium in the system. This is a preliminary study in order to observe the complexation behavior between Gd3+ and targeted molecules. This was carried out in 100 mM MES buffer at pH 5.5. The binding constant (Log K) of the Gd3+-PAR (1:1) complex at pH 5.5 is 4.41 ± 0.09 M-1. Since this method only uses UV-Vis spectrometry, it is concluded that colorimetric assay employing PAR is a fast and inexpensive method in order to analyze the binding activity between Gd3+ and targeted ligands. Keywords: Gadolinium, colorimetric assay, MRI contrast agent.